2021
DOI: 10.1088/2051-672x/abda93
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on tribological properties and air tightness of co-textured cylinder liner-piston ring on an engine tester

Abstract: The performance of cylinder liner-piston ring (CLPR) affects the efficiency of marine engine greatly. An experimental study on textured CLPR was conducted to seek insight into the operation reliability of CLPR. Three types of surface texture, groove texture on cylinder liner, dimple texture on piston ring, and co-texture on both sides, were processed. A series of tests were then carried out on an engine tester. Three characterization parameters, contact resistance, worn surface topography on cylinder liner, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The majority of frictional power losses in internal combustion engines are situated within the hydrodynamic lubrication regime in the mid-stroke, where the piston reaches its maximum velocity, leading to increased shear forces in the lubricating oil and, thus, higher viscous losses [28]. The surface finish of piston cylinder liners significantly influences the friction coefficient, the load-carrying capacity between the tribological pair of cylinder liners and piston rings, and the durability of the sealing rings [29,30]. Plateau honing is a surface finishing process in cylinder liners that removes the highest peaks of the liner surface, resulting in a reduced surface roughness, imparting a surface texture characterized by deep valleys that serve as lubricant reservoirs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of frictional power losses in internal combustion engines are situated within the hydrodynamic lubrication regime in the mid-stroke, where the piston reaches its maximum velocity, leading to increased shear forces in the lubricating oil and, thus, higher viscous losses [28]. The surface finish of piston cylinder liners significantly influences the friction coefficient, the load-carrying capacity between the tribological pair of cylinder liners and piston rings, and the durability of the sealing rings [29,30]. Plateau honing is a surface finishing process in cylinder liners that removes the highest peaks of the liner surface, resulting in a reduced surface roughness, imparting a surface texture characterized by deep valleys that serve as lubricant reservoirs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Surface texture could effectively reduce friction (Wang et al , 2023), and a reasonable texture density could reduce the friction by up to 13% compared with nontextured (Das and Kakoty, 2023). The tribological performance of the lower pair had been significantly improved by preparing the surface texture on its face (Miao et al , 2021; Nayab and Kakoty, 2021). Therefore, the sample with reasonable texture parameter design can effectively reduce friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al [ 27 ] found that dimples on the piston ring surface are better-accumulated lubricant than grooves on the cylinder liner. The dimpled texture of the piston rings led to a better increase in contact resistance than the grooved texture of the cylinder liners [ 28 ]. Rao et al [ 29 ] studied the tribological effect of the grooved cylinder liner accompanied by the dimpled piston ring radial surface and found that the first option reduced exhaust gas (Nox) emissions.…”
Section: Introductionmentioning
confidence: 99%